Virtual Reality Usage in Managing Pain Labor: A Scoping Review - Safitriana Safitriana; Yulius Tiranda; Nittaya Panngam (Disease Prevention and Public Health Journal, 2023)
Background: Labor is one of the most memorable experiences for mothers and families where the labor process might cause intense pain. The use of non-pharmacological therapy is currently an option in reducing the pain experienced, one of which is using Virtual Reality (VR). The aim of this study was to explore and investigate the use of VR in the management of labor pain. Method: 4 electronic databases were used, Ebsco, Pubmed, Science Direct, and Scopus. The used keywords were (pain labor OR pain delivery OR childbirth pain) AND (virtual reality OR augmented reality OR VR). Results: There were 7 articles that met the inclusion criteria where 2 studies used videos of animals swimming accompanied by natural sounds and classical music, 3 studies used videos of natural scenery, 1 study used videos of newborn babies and classical music, and 1 study used videos of ultrasound results fetus. Conclusion: Virtual reality can be used to help reduce pain during labor and has no impact on the mother and fetus